Lead shot incarceration in appendix: an unusual cause of appendicular foreign body. (23rd April 2013) - Munipalle, P C; Little, M; Garud, T
Abstract : A previously fit man was investigated for right-sided abdominal pain and an appendicular foreign body (FB) caused by ingested lead shot was found. He had associated urinary tract infection causing his symptoms and hence was treated conservatively. We present this rare case, followed by discussion of the causes, investigations, clinical significance and management of appendicular FBs.